Answer:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
3*(x+15)*23-(24)=0
Step by step solution :
STEP
1
:
Equation at the end of step 1
(3 • (x + 15) • 23) - 24 = 0
STEP
2
:
Equation at the end of step 2
69 • (x + 15) - 24 = 0
STEP
3
:
STEP
4
:
Pulling out like terms
4.1 Pull out like factors :
69x + 1011 = 3 • (23x + 337)
Equation at the end of step
4
:
3 • (23x + 337) = 0
STEP
5
:
Equations which are never true
5.1 Solve : 3 = 0
This equation has no solution.
A a non-zero constant never equals zero.
Solving a Single Variable Equation:
5.2 Solve : 23x+337 = 0
Subtract 337 from both sides of the equation :
23x = -337
Divide both sides of the equation by 23:
x = -337/23 = -14.652
Explanation: